Organic acid metabolism changes during postharvest dehydration process in grape (Vitis vinifera L.) berries - Soares, Flávio (2016)
Poster apresentado no "QualityFruit2016 - Final Annual Conference of the COST FA1106 action", no Porto, Portugal, 2016